AIGC Helps Students in Pre-education to Improve Digital Teaching Ability - Jiangli (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
To enhance the digital teaching capabilities of preschool education majors, Qingdao Hengxing University has constructed an AIGC technology integration path from three aspects: training system, teaching paradigm, and practical ecology. In terms of the training system, with the framework of "concept innovation - institutional guarantee - resource integration", it is incorporated into the professional development plan, a three-level linkage management mechanism is established, and government-industry-university-research- application collaboration is carried out to obtain resources. In the teaching paradigm, a three- tier curriculum matrix is built, integrating AIGC with general education, core courses, and innovative projects to achieve a balance between instrumental and value rationality. In the practical ecology, a practical training network connecting virtual simulation, campus practice, and kindergarten application is constructed. Through the virtual kindergarten system, maker space, and the "1+1+1" kindergarten practice model, it promotes the transformation of students’ technical application capabilities from theory to practice, providing support for the cultivation of digital talents in preschool education.